2013
DOI: 10.1016/b978-0-12-401676-7.00001-2
|View full text |Cite
|
Sign up to set email alerts
|

AEG-1/MTDH/LYRIC, the Beginning

Abstract: Since its initial identification as a HIV-1-inducible gene in 2002, astrocyte elevated gene-1 (AEG-1), subsequently cloned as metadherin (MTDH) and lysine-rich CEACAM1 coisolated (LYRIC), has emerged over the past 10 years as an important oncogene providing a valuable prognostic marker in patients with various cancers. Recent studies demonstrate that AEG-1/MTDH/LYRIC is a pleiotropic protein that can localize in the cell membrane, cytoplasm, endoplasmic reticulum (ER), nucleus, and nucleolus, and contributes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 109 publications
(282 reference statements)
0
32
0
Order By: Relevance
“…Astrocyte elevated gene-1 (AEG-1) was first identified as an upregulated transcript in primary human fetal astrocytes infected with HIV-1 or treated with TNF-α and later characterized as a major oncogene highly upregulated in a broad array of cancers including GBM (810). Subsequently, using in vivo phage screening the mouse AEG-1 gene was cloned and named met adherin (MTDH) based on its pro-metastasis role in tumor cell homing to lung (11).…”
Section: Introductionmentioning
confidence: 99%
“…Astrocyte elevated gene-1 (AEG-1) was first identified as an upregulated transcript in primary human fetal astrocytes infected with HIV-1 or treated with TNF-α and later characterized as a major oncogene highly upregulated in a broad array of cancers including GBM (810). Subsequently, using in vivo phage screening the mouse AEG-1 gene was cloned and named met adherin (MTDH) based on its pro-metastasis role in tumor cell homing to lung (11).…”
Section: Introductionmentioning
confidence: 99%
“…AEG- 1 was first identified using subtraction hybridization as an up-regulated gene in primary human fetal astrocytes infected with HIV-1 (6, 7). Subsequent studies identified AEG- 1 as a metastasis-associated gene in the mouse, called metadherin (MTDH) (8), and as a lysine-rich CEACAM1 co-isolated gene in the rat, called LYRIC (9).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have implied that an up-regulation of AEG-1 enhances characteristics of malignant aggressiveness making it an independent prognostic factor for unfavourable clinical outcome. This suggests that AEG-1 is valuable as a prognostic biomarker of disease progression and survival in patients with EC [16][17][18].…”
Section: Biomarkers With Diagnostic Prognostic and Therapeutic Valuementioning
confidence: 96%
“…AEG-1 is located at chromosome 8q22 [15] and is also known as metadherin (MTDH) and lysine-rich CEACAM1 coisolated (LYRIC) [17]. Since its discovery in 2002, as HIV-and TNF--α-inducible gene in primary human fetal astrocytes [15], several authors have described its tumor-promoting activity which is related to the activation of diverse signal transduction pathways (PI3K/ AKT, NF-κB, MEK/ERK, WNT/β-catenin) involved in cancer progression, in addition to its role in pathogenesis, metastasis, invasion, angiogenesis and overall patient survival [16]. It should be noticed that AEG-1 is an important oncogene were its expression status is firmly established in a subsequent array of cancers.…”
Section: Biomarkers With Diagnostic Prognostic and Therapeutic Valuementioning
confidence: 99%